Hybridization promotes color polymorphism in the aposematic harlequin poison frog, Oophaga histrionica (2013)
Whether hybridization can be a mechanism that drives phenotypic diversity is a widely debated topic in evolutionary biology. In poison frogs (Dendrobatidae), assortative mating has been invoked to explain how new color morphs persist despite the expected homogenizing effects of natural selection. Here, we tested the complementary hypothesis that new morphs arise through hybridization between different color morphs. Specifically, we (1) reconstructed the phylogenetic relationships among the studied populations of a dart-poison frog to provide an evolutionary framework, (2) tested whether microsatellite allele frequencies of one putative hybrid population of the polymorphic frog O. histrionica are intermediate between O. histrionica and O. lehmanni, and (3) conducted mate-choice experiments to test whether putatively intermediate females prefer homotypic males over males from the other two populations. Our findings are compatible with a hybrid origin for the new morph and emphasize the possibility of hybridization as a mechanism generating variation in polymorphic species. Moreover, because coloration in poison frogs is aposematic and should be heavily constrained, our findings suggest that hybridization can produce phenotypic novelty even in systems where phenotypes are subject to strong stabilizing selection. © 2013 The Authors. Ecology and Evolution published by John Wiley & Sons Ltd.